2017
DOI: 10.1103/physrevb.96.014418
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinarily large intrinsic magnetodielectric coupling of the Tb member within the Haldane spin-chain family R2BaNiO5

Abstract: The Haldane spin-chain compound, Tb2BaNiO5, has been known to order antiferromagnetically below (TN=) 63 K. The present magnetic studies on the polycrystals bring out that there is another magnetic transition at a lower temperature (T2=) 25 K, with a pronounced magnetic-field induced metamagnetic and metaelectric behavior. Multiferroic features are found below T2 only, and not at TN. The most intriguing observation is that the observed change of dielectric constant (Δε) is intrinsic and largest (e.g., ~ 18% a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
(81 reference statements)
2
20
0
Order By: Relevance
“…In general, this cross coupling is strong in the type-II MFs where the ferroelectricity appears due to particular kind of spin structure of the materials, as classified by Khomskii [3,4]. Owing to the mutually exclusive nature of magnetism and ferroelectricity, several mechanisms have been proposed so far to understand the origin of multiferrocity in type-II MFs, such as, breaking of the inversion symmetry through asymmetric Dzyaloshinskii-Moriya (DM) interaction, the strong spin-dependent p-d hybridization, the exchange striction, and the single-ion magnetic anisotropy [5][6][7][8][9][10][11][12][13]. However, this cross coupling of spin and charge can also lead to another aspect of the MFs i.e., the magnetoelectric coupling effect in the insulating materials apart from the proper ferroelectric polarization, which could facilitate the pathway to engineer memory devices based on this effect and enlighten our knowledge to model the cutting-edge multiferroic materials [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In general, this cross coupling is strong in the type-II MFs where the ferroelectricity appears due to particular kind of spin structure of the materials, as classified by Khomskii [3,4]. Owing to the mutually exclusive nature of magnetism and ferroelectricity, several mechanisms have been proposed so far to understand the origin of multiferrocity in type-II MFs, such as, breaking of the inversion symmetry through asymmetric Dzyaloshinskii-Moriya (DM) interaction, the strong spin-dependent p-d hybridization, the exchange striction, and the single-ion magnetic anisotropy [5][6][7][8][9][10][11][12][13]. However, this cross coupling of spin and charge can also lead to another aspect of the MFs i.e., the magnetoelectric coupling effect in the insulating materials apart from the proper ferroelectric polarization, which could facilitate the pathway to engineer memory devices based on this effect and enlighten our knowledge to model the cutting-edge multiferroic materials [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Upadhyay, Garcia-Matres, and Basu et al demonstrated this behavior for Tb 2 -BaNiO 5 , Dy 2 BaNiO 5 , and Er 2 BaNiO 5 nickelates, respectively. 10,15,18 The DBNO NC synthesized in this work were used as photocatalysts. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…17 Upadhyay et al studied the magnetic transitions of Tb 2 BaNiO 5 . 18 The Tb 2 BaNiO 5 has an AFM order below the Neel temperature (TN ¼ 63 K). In addition, Popova et al studied the magnetic structure and interchain interactions in the mixed-spin nickelate containing two different rare earth metals, (Er 0.25 Gd 0.75 ) 2 BaNiO 5 , using optical spectroscopy.…”
Section: Introductionsmentioning
confidence: 99%
“…Because of the 1D character several members of R 2 BaNiO 5 series exhibit Haldane gap in the excitation spectrum [10][11][12][13]. The multiferroic order associated with a significant magnetoelectric coupling has been proposed in some members of the R 2 BaNiO 5 series [14], such as Sm 2 BaNiO 5 [15], Dy 2 BaNiO 5 [16], Tb 2 BaNiO 5 [17], Er 2 BaNiO 5 [18], Gd 2 BaNiO 5 [19]. For Sm 2 BaNiO 5 a structural transition to a non-centrosymmetric Imm2 space group from the centrosymmetric Immm space group has been proposed for interpreting the ferroelectricity above magnetic ordering temperature [15].…”
Section: Introductionmentioning
confidence: 99%